(untitled) (Research, Society and Development, 2020)
The silver element (Ag) is present in the effluent of radiography equipment and because it is a bioaccumulating chemical species, it requires the proper management of its disposal, since if it is improperly directed to the water receiving body, it can compromise the biological chain. This study aimed to quantify the Ag content in the effluent of a radiography equipment, at three points of disposal, as well as to evaluate the effluent management process in the light of the relevant legislation. For this purpose, samples were collected at three points of disposal over three days after their generation, and the same ones were analyzed by Plasma Atomic Emission Spectrometry (ICP-EAP). The results revealed an average Ag content of 5.87 mg/L; 2,795.65 mg/L and 1,525.31 mg/L, for the developer, fixer and developer of the developer and fixer in water, respectively. The observed values are much higher than the maximum limit established by the legislation. It was also verified that the effluent management in the evaluated hospital unit is precarious, about the conditioning, storage and final destination of group B waste, since the establishment does not comply with all the premises listed by RDC/ANVISA number 306/2004.